Shift work and cardiovascular disease – pathways from circadian stress to morbidity - Puttonen, Sampsa; Härmä, Mikko; Hublin, Christer (Scandinavian Journal of Work, Environment & Health, 2010)
In order to establish a causal relation between shift work and cardiovascular disease (CVD), we need to verify the pathways from the former to the latter. This paper aims to review the current knowledge of the mechanisms between shift work and CVD. Shift work can increase the risk of CVD by several interrelated psychosocial, behavioral, and physiological mechanisms. The psychosocial mechanisms relate to difficulties in controlling working hours, decreased work–life balance, and poor recovery following work. The most probable behavioral changes are weight gain and smoking. The plausible physiological and biological mechanisms are related to the activation of the autonomic nervous system, inflammation, changed lipid and glucose metabolism, and related changes in the risk for atherosclerosis, metabolic syndrome, and type II diabetes. The data provide evidence for possible disease mechanisms between shift work and CVD, but compelling evidence on any specific mechanism is missing.
Keywords: cardiovascular disease; circadian stress; coronary heart disease; CVD; health; literature review; morbidity; review; shift work; stress; workhours; working hours